Latvijas mazo uzņēmumu vadīšanas īpatnības - Kantāne, Ināra (Latvijas Universitāte, 2013)
Mazie uzņēmumi veido lielāko daļu uzņēmumu Latvijā, un tajos ir nodarbināti vairāk nekā puse iedzīvotāju darbspējīgā vecumā. Mazo uzņēmumu attīstības jautājumi ir īpaši aktuāli situācijā, kad globalizācijas rezultātā pieaugusi starptautiskā konkurence, augušas kvalitātes prasības produktiem un pakalpojumiem, pieaudzis bezdarbs. Pasaulē veiktie zinātniskie pētījumi liecina, ka vāja mazo uzņēmumu vadīšana ir viens no galvenajiem iemesliem, kādēļ uzņēmumu darbības rezultāti pasliktinās un uzņēmumi tiek likvidēti. Promocijas darba mērķis ir izpētīt mazo uzņēmumu vadīšanu nozīmīgi ietekmējošos faktorus un to savstarpējās ietekmes kopsakarības, izpētīt mazo uzņēmumu vadītāju uzskatus par izglītības un prasmju uzņēmuma vadīšanā nozīmīgumu, atklāt iespējas mazo uzņēmumu vadīšanas pilnveidošanai. Promocijas darba pirmajā nodaļā analizēta akadēmiskā literatūra un jaunākie zinātniskie pētījumi par mazo uzņēmumu vadītāju zināšanu un prasmju nozīmīgumu uzņēmuma vadīšanā, vadītāja personisko īpašību nozīmīgumu, mazo uzņēmumu vadīšanas īpatnībām, kā arī ārējās vides ietekme uz mazo uzņēmumu vadīšanu. Nodaļā analizēti zinātniskie pētījumi par uzņēmuma klimata nozīmīgumu uzņēmumos un to ietekmējošiem faktoriem, kā arī par zināšanu vadības nozīmīgumu organizācijās un zināšanu vadības nepieciešamību mazos uzņēmumos. Otrajā nodaļā pētīta mazo uzņēmumu attīstība un īpatnības Latvijā, izpētīta valdības politika mazo uzņēmumu atbalstam, analizēti valsts atbalsta pasākumi un ES fondu atbalsts maziem uzņēmumiem, analizēta uzņēmējdarbības izglītības īstenošana augstākās izglītības iestādēs. Promocijas darba trešajā nodaļā autore pētījusi, kā uzlabot mazo uzņēmumu vadīšanu Latvijā. Izpētīti ir mazo uzņēmumu vadītāju uzskati par uzņēmējdarbības izglītības un pieredzes nozīmīgumu. Noskaidrots, kādi ir mazo uzņēmumu vadītāju uzskati par apmācību, motivācijas un komunikācijas nozīmīgumu uzņēmumā. Analizētas vadītāju uzskatu atšķirības Latvijas reģionos, kā arī tautsaimniecības nozaru griezumā un arī atkarībā no uzņēmuma lieluma un vadītāja dzimuma. Izpētītas vadītāju apmācību, motivācijas, komunikācijas nozīmīguma vērtējumu savstarpējās sakarības un saistība ar uzņēmuma inovatīvās darbības vērtējumu. Pētīta interneta lietošanas aktivitāte mazos uzņēmumos, sīkāk izpētītas interneta lietošanas aktivitātes atšķirības Latvijas reģionos, kā arī atkarībā no nozares un uzņēmuma lieluma. Nodaļā analizēti mazo uzņēmumu vadītāju viedokļi par valsts atbalsta pasākumu, nodokļu politikas, finanšu resursu pieejamības, ārējās vides stabilitātes, administratīvo procedūru, kā arī informācijas pieejamības atbalsta pasākumiem nozīmīgums. Noteikti galvenie spēki, kas ietekmē mazos uzņēmumus. Pamatojoties uz zinātniskās literatūras analīzi un empīriskā pētījuma rezultātiem, atklātas mazo uzņēmumu vadīšanas pilnveidošanas iespējas. Promocijas darba pamata saturs ir izklāstīts 194 lappusēs. Darbā ievietoti 28 attēli un 11 tabulas. Literatūras un avotu sarakstā iekļautas 228 vienības. Promocijas darbam ir 7 pielikumi.

Small enterprises account for the majority of enterprises in Latvia and employ more than a half of the working age population. The development issues of the small enterprises are particularly topical in the situation when as a result of globalization international competition has increased, higher quality is required from products and services, qualification requirements towards businesses are becoming tenser, and there has been a rise in unemployment. The globally conducted scientific research suggests that poor management of small businesses is one of the key reasons why the performance of these enterprises is deteriorating and the businesses are liquidated. The aim of the promotion paper is to study the factors which considerably influence the management of small businesses and regularities of their mutual interaction and to study the opinions of the managers of small businesses about the role of education and skills in corporate management and identify the opportunities for the improvement of corporate management. The first chapter of the promotion paper analyses academic literature and latest scientific research on the role of a small business managers’ knowledge and skills of corporate management, the importance of the manager’s personal qualities, key actions of small business managers in managing their enterprises as well as the influence of the external environment on the management of small businesses. The chapter analyses the research on the corporate climate in small enterprises and the factors influencing the climate as well as the importance of knowledge management as well as the role of knowledge management in organizations and the need for knowledge management in small businesses. The second chapter explores the development and peculiarities of small businesses in Latvia and studies the government policy for the support of small businesses as well as analyses the national support measures and EU support to small enterprises. The chapter also deals with the implementation of business administration education in the tertiary and vocational education institutions in the study programmes not focusing on economics and business administration. In the third chapter of the promotion paper the Author has studied the possibilities of improving the management of small businesses in Latvia. The research has also been made of the opinions of the small business managers about the importance of business management education and experience. The Author has studied and identified the opinions and differences in the opinions of small business managers about the role of training, motivation and communication in an enterprise. The differences of opinions have been examined in the cross-section of the regions of Latvia and industries as well as depending on the size of the enterprise and the manager’s gender. The Author has studied the mutual correlations and relations of the assessments of training, motivation and communication importance on the innovative performance of a company. Other aspects under study are the intensity of the use of the Internet in small enterprises, differences in the intensity of using the Internet in the regions of Latvia as well as depending on the industry and size of the enterprise. The chapter analyses the opinions of small business managers about 54 the influence of state support measures, tax policy, availability of financial resources, stability of the external environment, influence of administrative procedures as well as availability of information on support measures. The Author has identified the key forces influencing small enterprises. Based on the analysis of scientific literature and empirical research results improvement opportunities of small business management have been revealed. The main contents of the promotion paper covers 190 pages. It contains 28 figures and 11 tables. The list of references contains 228 items.
Management individualities for small enterprises in Latvia
Elektroniskā versija nesatur pielikumus
Keywords: Vadībzinātne; mazo uzņēmumu vadīšana; uzņēmējdarbības izglītība; motivācija; komunikācija; Small business (Management)